Stem Cells Therapy for COVID-19: A Systematic Review and Meta-Analysis - Arabpour, Erfan; Khoshdel, Sina; Tabatabaie, Negin; Akhgarzad, Ali; Zangiabadian, Moein; Nasiri, Mohammad Javad (Frontiers in Medicine, 2021)
Introduction: Vaccination seems to be a good solution for preventing and controlling coronavirus disease (COVID-19) pandemic, but still there are some challenges in COVID-19 vaccination. Investigating new therapeutic options for COVID-19 is necessary. The current study aimed to evaluate the safety and efficacy of stem cells in treating patients with COVID-19. Methods: We reviewed the relevant scientific literature published up to April 1, 2021. The pooled risk ratio (RR) with 95% CI was assessed using a fixed or random-effect model. We considered P < 0.05 as statistically significant for publication bias. Data were analyzed by Comprehensive Meta-Analysis software, Version 2.0 (Biostat, Englewood, NJ). Results: After reviewing 1,262 records, we identified 10 studies that met the inclusion criteria. The analysis showed that stem cell therapy could significantly reduce the mortality rate (RR 0.471, 95% CI: 0.270–0.821) and morbidity (RR 0.788, 95% CI: 0.626–0.992) in patients with COVID-19; compared with the control group. Conclusions: The present study suggests that stem cell therapy has a remarkable effect on reducing mortality and morbidity of patients with COVID-19. Further large-scale studies are needed to approve these results. Defining a protocol for stem cell therapy in patients with COVID-19 can lead to achieving the best clinical outcomes.